2020
DOI: 10.13106/jafeb.2020.vol7.no7.413
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workforce Restructuring on Withdrawal Behavior: The Role of Job Insecurity, Career Plateau and Procedural Justice

Abstract: This study examines the direct effect of workforce restructuring on the withdrawal behavior and mediating effect of perceived job insecurity. Empirically it also explores the moderating effect of career plateau and procedural justice on the above relationship. The study focuses on the mediating role of job insecurity and the moderating role of career plateau in relations to procedural justice, which will concentrate on the relationship between workforce restructuring and withdrawal behavior. For the empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…With the increase in the employees downsizing in the hotel industry, employees feel stressed either because of the fear of being laid off or unclear job descriptions. In addition to that, restructuring the workforce causes an increase in job insecurity among employees, resulting in employees' withdrawal behavior (Ghaderi et al , 2021; Park et al , 2020). Previous studies have revealed that employees' behaviors and attitudes are affected by job insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the employees downsizing in the hotel industry, employees feel stressed either because of the fear of being laid off or unclear job descriptions. In addition to that, restructuring the workforce causes an increase in job insecurity among employees, resulting in employees' withdrawal behavior (Ghaderi et al , 2021; Park et al , 2020). Previous studies have revealed that employees' behaviors and attitudes are affected by job insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…If it is not, then highly employable workers can believe they are not adequately paid for their contributions and thus suffer a psychological violation of the contract. This has certain adverse effects, such as decreased loyalty, organizational engagement, job satisfaction, and motivation at work [48]. According to a different study, the connection between perceived employability and optimal functioning (i.e., in-role success and supportive behavior) is much less than the rate of perceived job insecurity [49].…”
Section: Moderating Role Of Job Insecuritymentioning
confidence: 99%